The Influence of the Nabelan-Kabelan Myth on Christian Acceptance in the Baliem Valley - abed nego tabuni (CENDERAWASIH: Jurnal Antropologi Papua, 2025)
Nabelan-Kabelan mythology is a belief system of the Lani people in the interior of the central mountains of Papua future which is integrated into a culture rooted in oral stories that are lived through the symbol of Wabir, (They), Pirikur, (Bird) and Wip tree. This research aims to reveal how Nabelan-Kabelan was formed and played an important role in the process of encounter between culture and Christianity. The method used in this research is an ethnographic method with a social history approach, research data sources were obtained through observation, interviews and literature reviews. Primary data sources were obtained from figures belonging to the group of traditional elders, religious leaders and the community who have connections with the research topic. Based on the research results, it can be seen that this myth has a big impact on the acceptance of Christianity, which gives legitimacy to Christianity to convert important elements in culture into a theological narrative.